2017
DOI: 10.11598/btb.2017.24.1.621
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Services of Agroforestry Landscapes in Selected Watershed Areas in the Philippines and Indonesia

Abstract: This article argues that the practice of agroforestry provides ecological contributions to the smallholder farmers cultivating in the watershed areas. Specifically, this farming system provides contribution to carbon sequestration potential of the woody perennials and the biodiversity conservation of the other components of the system. This argument is based on the research conducted in Molawin-Dampalit Sub-Watershed, Mt. Makiling Forest Reserve in the Philippines and Way Betung Watershed in Indonesia. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Agroforestry has contributed to strengthening smallholder farmers' resilience to climate change in Indonesia by offering 20% more food variety in the traditional pattern and a fivefold income increase in the commercial pattern [22]. Agroforestry systems also provide environmental service benefits, such as increasing soil organic content; improving soil health through nutrient repair and fertility processes; improving soil biological dynamics; improving soil carbon sequestration and climate change mitigation; and improving water quality, climate change mitigation, and adaptation [39,45,46]. Some of the benefits related to soil nutrients and fertility, as well as soil carbon sequestration, can be obtained from minimal or no-tillage practices, even without trees.…”
Section: Existing Conditions Of Agroforestry In Indonesiamentioning
confidence: 99%
See 2 more Smart Citations
“…Agroforestry has contributed to strengthening smallholder farmers' resilience to climate change in Indonesia by offering 20% more food variety in the traditional pattern and a fivefold income increase in the commercial pattern [22]. Agroforestry systems also provide environmental service benefits, such as increasing soil organic content; improving soil health through nutrient repair and fertility processes; improving soil biological dynamics; improving soil carbon sequestration and climate change mitigation; and improving water quality, climate change mitigation, and adaptation [39,45,46]. Some of the benefits related to soil nutrients and fertility, as well as soil carbon sequestration, can be obtained from minimal or no-tillage practices, even without trees.…”
Section: Existing Conditions Of Agroforestry In Indonesiamentioning
confidence: 99%
“…However, the presence of trees in agroforestry systems can add more benefits. The presence of trees and perennial plants in agroforestry produces the highest aboveground carbon stocks, including belowground carbon stocks, thereby improving carbon sequestration and mitigating climate change [23,39]. Trees in agroforestry also enhance soil organic content, increase soil nutrients and fertility, and increase soil microbial dynamics, which have a positive effect on soil health [45].…”
Section: Existing Conditions Of Agroforestry In Indonesiamentioning
confidence: 99%
See 1 more Smart Citation
“…This local knowledge is validated by science. Besides providing as additional food and income source, trees, in general, provide ecological services, such as carbon sequestration (Casas et al 2014;Palma and Carandang 2014;Marin et al 2015;Baliton et al 2017;Tabal and Mendoza 2020;Sharma et al 2021), and enhancement of biological diversity (Amoroso et al 2012;Malabrigo 2013;Baliton et al 2017).…”
Section: Integrating Trees On the Farmmentioning
confidence: 99%
“…In their study, Maraseni et al (2022) revealed that agroforestry practices in home gardens were among the key alternatives for smallholders during COVID-19. This could be because agroforestry has always been recognized for its ecological services (Baliton, et al, 2017;Baliton et al, 2020;Palma & Carandang, 2014;and socioeconomic contributions (Tolentino et al, 2010;Landicho et al, 2017). However, the livelihoods of some agroforestry farmers were negatively affected by the pandemic because of the reduced farm income brought about by the difficulty in marketing their products, and the reduction in farm productivity in communities in Indonesia (Pieter et al, 2022).…”
Section: Introductionmentioning
confidence: 99%